Boletim Atlas ODS Amazonas V.2 N.5 - Especial COVID-19 - Pereira, Henrique dos Santos (Brasil, 2020)
The Special Edition of SDG Amazonas Atlas Report was created to present reflections and projections, in addition to maps and illustrations, of the coronavirus pandemic of the State of Amazonas. The document counts on the collaboration of researchers from different areas who present their perspectives around the specificities of the State.